Asymptotic expressions of normalized laguerre matrix polynomials on bounded intervals - Jódar L.; Sastre J. (Utilitas Mathematica, 2004)
This paper deals with the asymptotics of normalized Laguerre matrix polynomials of a complex matrix parameter on bounded intervals in the positive real line. Asymptotic expressions of Laguerre matrix polynomials and their derivatives expressed in terms of trigonometric matrix functions are proposed.